2013
DOI: 10.1038/embor.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

Human Primpol1: a novel guardian of stalled replication forks

Abstract: Huang and colleagues identify a human primase‐polymerase that is required for stalled replication fork restart and the maintenance of genome integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Besides SLFN11, RPA interacts with a large number of proteins involved in DNA replication, cell cycle regulation, and DNA repair and has been considered as a platform that promotes critical biochemical reactions that occur at ssDNA. For example, we and several other groups have demonstrated that hPrimpol1/CCDC111/Primpol , the PSO4/PRP19 complex , HARP/SMARCAL1 , and several other proteins possessing enzymatic activities can be recruited to sites of DNA damage through the direct interaction with RPA. While SLFN11 inhibits checkpoint maintenance and HR repair, almost all the known RPA‐binding proteins positively regulate DNA damage response.…”
Section: Discussionmentioning
confidence: 96%
“…Besides SLFN11, RPA interacts with a large number of proteins involved in DNA replication, cell cycle regulation, and DNA repair and has been considered as a platform that promotes critical biochemical reactions that occur at ssDNA. For example, we and several other groups have demonstrated that hPrimpol1/CCDC111/Primpol , the PSO4/PRP19 complex , HARP/SMARCAL1 , and several other proteins possessing enzymatic activities can be recruited to sites of DNA damage through the direct interaction with RPA. While SLFN11 inhibits checkpoint maintenance and HR repair, almost all the known RPA‐binding proteins positively regulate DNA damage response.…”
Section: Discussionmentioning
confidence: 96%
“…Cells depleted of PrimPol display an increase of spontaneous DNA damage and are defective in restarting stalled replication forks ( Wan et al, 2013 ). Thus, it is believed to be an important player in bypassing DNA lesions and restarting stalled replication ( Im et al, 2013 ). The recruitment of PrimPol to stalled forks seems to be via its direct interaction with the OB-C domain of RPA ( Wan et al, 2013 ).…”
Section: Rpamentioning
confidence: 99%
“…lesions and restarting stalled replication (Im et al, 2013). The recruitment of PrimPol to stalled forks seems to be via its direct interaction with the OB-C domain of RPA (Wan et al, 2013).…”
Section: Rpa In Regulating Activities Of Other Polymerases/helicases mentioning
confidence: 99%
“…It possesses both primase and DNA polymerase activities in vitro and is recruited to sites of DNA damage and stalled replication forks through its direct interaction with RPA1 [57][58][59][60][61][62]. Evidence has indicated that RPA1 binding is required for the cellular function of hPrimol1 in response to DNA replication stress [57][58][59][60][61][62].…”
Section: Rpa and Dna Replicationmentioning
confidence: 99%
“…hPrimpol1 is a recently identified DNA primase-polymerase that is involved in the response to DNA replication stress [54][55][56][57][58][59][60][61][62]. It possesses both primase and DNA polymerase activities in vitro and is recruited to sites of DNA damage and stalled replication forks through its direct interaction with RPA1 [57][58][59][60][61][62].…”
Section: Rpa and Dna Replicationmentioning
confidence: 99%